PEMBERIAN KOMBINASI PUPUK KANDANG DENGAN NPKPADA PERTUMBUHANTANAMAN SORGUM (Sorghum bicolor (L.) Moench) - Basri, Hasan; Pusfita, Fifi; Saputra, Sukemi Indra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sorghum (Sorghum bicolor (L.) Moench) is one of the cereal plants enriched by source of carbohydrates and protein. This study aimed to determine the effect of manure with NPK fertilizer combination to get the best combination of manure fertilizer with NPK on growth of sorghum (Sorghum bicolor (L.) Moench). Research has been conducted on the Pangkalan Baru Village, District Siak Hulu, from January to April 2014. This study used a randomized block design (RBD) consisting of 3 treatments and 6 group. Thus obtained 18 experimental units. The treatment given is chicken manure, goat manure and NPK fertilizer. Parameters measured were plant height, stem diameter, leaf number, days to flowering and panicle length. The data obtained were analyzed using ANOVA and proceed with further testing using the least significant difference (LSD) at 5% level. From the research that has been conducted granting combination of manure fertilizer with NPK fertilizer was significantly affecting the growth of plant height, stem diameter, leaf number, days to flowering and panicle length sorghum (Sorghum bicolor (L.) Moench). Giving of chicken manure with NPK fertilizer on a dose of 2 tons/ha and 600 kg/ha had given the best growth sorghum (Sorghum bicolor (L.) Moench). Keywords: Manure fertilizer,NPK fertilizer, Sorghum.